APPLICATION OF THE PROJECT-BASED LEARNING MODEL TO IMPROVE INDONESIAN LANGUAGE LEARNING OUTCOMES FOR CLASS V ELEMNTARY SCHOOL STUDENTS - Pangkey, Celline; Lengkong, Jeffry; Legi, Mozes; Rorimpandey, Widdy H. F. (Institut of Shanti Bhuana, 2023)
This research was conducted to address the issues that occur in the classroom and determine the extent of improvement in students' learning outcomes in the Indonesian language, particularly in the Pantun material, using the Project Based Learning model for the fifth-grade students at SD GMIM 4 Tomohon for the academic year 2022/2023, with a total of 31 students. The background of this research arises from the low learning outcomes of the fifth-grade students at SD GMIM 4 Tomohon, especially in the Pantun subject, due to the suboptimal application of the learning model. Based on observations conducted in the fifth-grade class at SD GMIM 4 Tomohon, out of 31 students, only eight have achieved the minimum completeness criteria (KKM) of 75. In contrast, 23 students did not meet the minimum completeness criteria set. This action research refers to the research design by Kemmis and Mc. Taggar has the following steps: Planning, Action, Observation, and Reflection, carried out in two cycles. Based on the percentage of learning outcomes obtained in Cycle I, which is 69%, it requires re-planning for Cycle II. In Cycle II, the learning outcomes have reached 86.2%, indicating an improvement and achievement of the completeness standard. With these results, the researcher can conclude that implementing the Project Based Learning model has increased students' learning outcomes. Based on the research and discussion, students' learning outcomes in the Indonesian language can be improved by applying the Project Based Learning model, especially in the Pantun material.